Effect of oxidized dextran on rat hepatocytes in toxic hepatosis of mixed etiology - V. A. Shkurupiy; M. A. Karpov; V. D. Klochin (Сибирский научный медицинский журнал, 2021)
The aim of research was to study the oxidized dextran protection effect against hepatic parenchyma defect at combinated acute and chronic toxicity of ethyl alcohol and tetrachloromethane solutions. Materials and methods. 150 male Wistar rats were injected by toxicants with intraperitoneal administration: 50 % CCl4 in olive oil solution and 5 % oxidized dextran (OD) aqueous solution with molecular weight 40 kDa and peroral 6.5 % ethyl alcohol aqueous solution. Tetrachloromethane was injected once a day, and then only ethyl alcohol aqueous solution was administrated 1 time per day during 3 days. The ethyl alcohol aqueous solution was not administered on the days of the of tetrachlomethane and OD injections. OD has been administered from the 1st day of the toxicants injection till 60 days. OD without toxicants has been injected for the next 30 days. Results and discussion. In animals that were injected only with toxicants, hepatocytes were in a state of vacuolar dystrophy, which occupied slightly more than 40 % of the organ parenchyma, and hepatocytes in a state of necrosis, which occupied from 37 to 28 % of the parenchyma at different periods of observation. The OD inclusion in the scheme for the prevention of necrotic complications reduced them from 3 to 4 times more than in animals that did not receive OD. The data obtained indicate the OD high hepatoprotective effectiveness.